Isolated Avulsion of the Tendon of Insertion of the Infraspinatus and Supraspinatus Muscles in Five Juvenile Labrador Retrievers - Mikola, Karoliina; Piras, Alessandro; Hakala, Laura (Veterinary and Comparative Orthopaedics and Traumatology, 2018)
Case History Five juvenile Labrador Retrievers between the ages of 6 and 8 months were presented to our referral centres with a history of intermittent forelimb lameness.Clinical Examination The clinical examination revealed the presence of bilateral orthopaedic problems in four out of five cases.Diagnostic Imaging Findings Radiographic and computed tomography examinations showed the presence of a radiolucent defect corresponding to the area of insertion of the infraspinatus or supraspinatus tendons on the proximal humerus. Three dogs were concurrently affected by elbow disease on the contralateral forelimb and one dog with bilateral infraspinatus avulsion also had osteochondritis dissecans affecting both shoulder joints.Diagnosis Avulsion of the insertion of the infraspinatus tendon in four dogs and of the supraspinatus tendon in one dog.Clinical Relevance According to the current literature, the incidence of infraspinatus and supraspinatus tendinopathies in adult Labrador Retrievers is higher than in other breeds. In our five cases, the patients were juvenile and the nature of the injury was an avulsion of the tendinous insertion. Avulsion of the tendon of insertion of the infraspinatus or supraspinatus has been poorly described in the veterinary literature, and this would represent the first series of cases affecting juvenile Labrador Retrievers.
Keywords: infraspinatus tendon; supraspinatus tendon; tendon avulsion; Labrador Retriever; canine; orthopaedic